2020
DOI: 10.14334/jitv.v25i2.2467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silybum marianum Aqueous Extract and L-carnitine on Stereological Changes in Diazinon-Treated Rat Liver

Abstract: As an organophosphorus, Diazinon (DZN) impairs liver tissue function by inhibiting acetylcholinesterase and causing oxidative stress. In this study, the effects of <em>Silybum</em><em> marianum </em>aqueous extract (SMAE) and L-carnitine (LC) on the stereological and histopathological changes of the liver in DZN-treated male rats were investigated. The rats in this study were placed into 9 groups of 8 each containing control, placebo, and a combination of DZN, SMAE, and LC. The animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
0
0
1
Order By: Relevance
“…From literature reviewed, it was found out that post-administration of silymarin milk thistle on carbon tetrachloride induced liver fibrosis, liver morphological parameters were greatly improved, leading to resolution of liver fibrosis (Tsai et al, 2008), hence concurring with this present study that demonstrates restorative effects of silymarin milk thistle on paracetamol-induced hepatotoxicity. Upon administration of silymarin milk thistle to diazinon-treated rats, it was found that liver volume and weight increased significantly as compared to those that never received silymarin, concurring with this study that liver volume and weight were positively impacted by the administration of silymarin milk thistle (Masoumi et al, 2020).…”
Section: Terminal Body Weight Of the Adult Albino Ratssupporting
confidence: 89%
“…From literature reviewed, it was found out that post-administration of silymarin milk thistle on carbon tetrachloride induced liver fibrosis, liver morphological parameters were greatly improved, leading to resolution of liver fibrosis (Tsai et al, 2008), hence concurring with this present study that demonstrates restorative effects of silymarin milk thistle on paracetamol-induced hepatotoxicity. Upon administration of silymarin milk thistle to diazinon-treated rats, it was found that liver volume and weight increased significantly as compared to those that never received silymarin, concurring with this study that liver volume and weight were positively impacted by the administration of silymarin milk thistle (Masoumi et al, 2020).…”
Section: Terminal Body Weight Of the Adult Albino Ratssupporting
confidence: 89%
“…Hasil yang diperoleh kontradiksi dengan penelitian lain yang melaporkan bahwa esensial oil dari beberapa tanaman memiliki aktivitas antioksidan dan dapat digunakan dalam pencegahan toksisitas diazinon (Al-Attar, Elnaggar and Almalki, 2017). Selain itu dilaporkan juga bahwa L-carnitin dan Silybum marianum yang memiliki aktivitas antioksidan dapat memberikan perlindungan pada jaringan hati dan mengurangi cedera hati akibat induksi diazinon pada tikus (Masoumi, Shariati and Mokhtari, 2020). Peningkatan kadar AST dan ALT pada tikus dalam penelitian ini mengindikasikan terjadi kerusakan jaringan hati akibat induksi diazinon.…”
Section: Pembahasanunclassified